Promoting heart regeneration via cardiomyocyte-specific OSKM-expression - Chen, Yanpu; Justus Liebig University Giessen (My University, 2022)
Cardiomyocytes are critically responsible for heart contraction and the pumping of blood through the circulatory system. In adult mice and humans, the rate of cardiomyocyte division is extremely low. In addition, dedicated cardiac stem cells that support myocardial renewal do not exist. Therefore, cardiomyocytes that are lost upon heart damage cannot be replenished. The inability to recover from cardiac injury, such as a myocardial infarction, is a leading cause of morbidity and mortality worldwide. Obviously, it is of great biomedical interest to find ways for enabling heart regeneration by restoration of lost cardiomyocytes. Previous reports have suggested that dedifferentiation of adult cardiomyocytes, which concurs with reactivation of fetal gene expression programs, is a prerequisite to enable adult cardiomyocytes to reenter the cell-cycle. Continuous forced expression of reprogramming factors known as OSKM (Oct4, Sox2, Klf4 and c-Myc) causes stepwise dedifferentiation of somatic cells and acquisition of pluripotency. More recently, it was shown that short-term OSKM-expression allows partial reprogramming of cells without the loss of cellular identity, improving the regenerative potential of tissues. The aim of this thesis was to investigate whether OSKM-expression in cardiomyocytes enforces cardiomyocyte dedifferentiation and proliferation, and to establish a cardiomyocyte-specific partial reprogramming strategy that might enable heart regeneration. To this end, two transgenic mouse lines designated i4FHeart and i4FHeart/mCherry were generated and analyzed in this study. These animal models allow control of OSKM expression specifically in fluorescently labelled cardiomyocytes. Here, it was found that OSKM-expression facilitates division of both neonatal and adult cardiomyocytes in vitro. Furthermore, cardiomyocyte-specific OSKM-expression results in dedifferentiation and enhanced proliferation of cardiomyocytes in neonatal, juvenile and adult hearts in vivo. Sustained OSKM-expression leads to complete cardiomyocyte reprogramming and heart tumor formation. Transient OSKM-expression in the adult heart dedifferentiates adult cardiomyocytes to fetal-like cardiomyocytes and allows subsequent reversion to the previous differentiated state. Transient OSKM-expression in juvenile mice enables heart regeneration after resection of the heart apex. In adult mice, transient OSKM-expression before and during myocardial infarction facilitates heart regeneration and ameliorates heart failure.
Keywords: cardiomyocytes; dedifferentiation; proliferation; re-differentiation; reprogramming; OSKM; regeneration; ddc:570